Social Capital Dynamics in Resolving Transition Conflict: Tourism to Mining in Pangkal Niur Village - Herdiyanti, Herdiyanti; Suyanto, Bagong; Mas'udah, Siti (AIBPM Publisher, 2023)
This study explores the pivotal role of social capital in managing conflicts during the transition from tourism to mining in Pangkal Niur Village. Using qualitative methods within a descriptive research framework, this study interviewed diverse stakeholders, including community leaders, the village government, tourism sector representatives, and opponents of this shift. Employing purposive sampling and inductive analysis, our findings reveal the significant role of social capital in mitigating conflicts between the tourism and mining sectors, particularly in the context of modernization and globalization. This holds profound implications for Pangkal Niur’s local community. The study underscores that social relationships form the basis for trust, cooperation, and community involvement, which is crucial for post-mining land restoration efforts. In regions with a significant mining sector like Bangka Belitung, these findings are highly relevant, emphasizing social capital as a catalyst for conflict resolution, promoting sustainable practices, safeguarding the environment, and enhancing community well-being in environmental management and sustainable development.